Evaluasi Implementasi sistem Informasi Keuangan Daerah Menggunakan Pendekatan Human, Organization, Technology Fit Model - Fandy Ardi Wijaya; Praptini Yulianti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to evaluate the implementation of the Regional Financial Information System (SIKD) in the East Java Provincial Government using the Human, Organization, Technology (HOT) Fit Model approach. This approach assesses system alignment from three key dimensions: human, organization, and technology, and analyzes their influence on the system's net benefit. A quantitative method was applied by distributing questionnaires to 100 respondents who are civil servants operating the expenditure and revenue management modules of the SIKD. Data analysis using Partial Least Squares (PLS) reveals that system quality, information quality, and service quality significantly affect system use, user satisfaction, and organizational structure. Furthermore, system use, user satisfaction, and organizational structure significantly influence the net benefit of SIKD utilization. The study concludes that SIKD implementation is generally effective but still requires improvements, particularly in service quality aspects. These findings are expected to serve as a foundation for optimizing SIKD to support transparent and accountable regional financial management effectively and efficiently.